2021
DOI: 10.1016/j.eprac.2021.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Risk Factors of Pulmonary Hypertension in Patients With Hyperthyroidism

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 37 publications
(37 reference statements)
0
4
0
1
Order By: Relevance
“…Possible mechanisms include endothelial injury due to increased cardiac output, elevated pulmonary vascular resistance induced by increased metabolism of intrinsic pulmonary vasodilating substances, and autoimmune-mediated endothelial remodelling 11. Recent studies have suggested that high free T4 and/or TRAb levels are risk factors for PH due to hyperthyroidism 5 12 13. However, in our patient with severe PH, TRAb was positive but at relatively low levels.…”
Section: Discussionmentioning
confidence: 51%
“…Possible mechanisms include endothelial injury due to increased cardiac output, elevated pulmonary vascular resistance induced by increased metabolism of intrinsic pulmonary vasodilating substances, and autoimmune-mediated endothelial remodelling 11. Recent studies have suggested that high free T4 and/or TRAb levels are risk factors for PH due to hyperthyroidism 5 12 13. However, in our patient with severe PH, TRAb was positive but at relatively low levels.…”
Section: Discussionmentioning
confidence: 51%
“…However, they did report higher T4 levels to be significantly associated with the development of PHTN. [ 14 ] In our review’s patient population (PHTN with HTH), TSH, T3, or T4 levels did not show any statistically significant association with outcomes of PHTN. This could indicate that although a more severe HTH is associated with PHTN, once it develops, the severity of HTH does not affect the reversibility of PHTN.…”
Section: Discussionmentioning
confidence: 64%
“…There are multiple retrospective studies, but mostly with small sample sizes; hence, the results have not been consistent. [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] Some studies have shown an association of hormone levels such as free thyroxine (FT [4] ), and antibodies such as TRAB with increased pulmonary pressures, whereas other studies did not find this association. [12,15,16,[18][19][20] Additionally, the pathophysiology of PHTN in HTH remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, increased TB was an independent predictor of PH in COPD patients living at HA and LA; COPD-PH patients from HA had significantly higher TB than those from LA. Similarly, some studies on TB and PH reported that PASP levels were positively correlated with TB, and TB was an independent predictor of PH, [ 67 , 68 ] the reasons could be that HA is characterized by hypoxia and bilirubin is an endogenous antioxidant molecule related to oxidative stress [ 69 , 70 ]. Moreover, in our study, transaminases between COPD-PH at HA and COPD-PH at LA were not significantly different, indicating that serum bilirubin was more sensitive to hemodynamic changes than transaminases, [ 71 ] however, the sensitivity of serum bilirubin and transaminases to altitude changes were required for assessment in more studies.…”
Section: Discussionmentioning
confidence: 99%